Benchmarking Software dan Website Report untuk Memudahkan Kategorisasi Device Berbasis Android Berdasarkan Performa - Michael Christian Tjandra; Justinus Andjarwirawan; Henry Novianus Palit (Jurnal Infra, 2015)
The popularity of Android based device could lead into an abundant amount of device choices from many vendors. There’s a lot factors that one needed to consider before they can decide one device on the market that fully coping their needs. Some of whice are device’s performance, size, and price. The benchmark application will put the device into trial which consists of CPU computation, JavaScript performance, Graphics, and Storage capability. Application aside, there will be a web service intended to provide service for masses in an easier and a simpler way.Based on the test results, the application can run well and can perform all of its functions. Score output are relevant and can give the user general view about the performance from the device on the market. On several later iteration of android version, usage permission for external storage are very limited. Hence, DriveSpeed2 can’t be run because the application couldn’t write on external storage freely.